Vocational Development and Life Project: Perspectives of Students and Professionals of Diversified Education in Costa Rica - Hernández Sanabria , Marcela (2025)
The article presents the findings of a research study conducted by the Psychopedagogy Department of the Universidad Estatal a Distancia (UNED) between 2023 and 2024. The main objective was to analyze vocational training and career choice among students in their final year of upper secondary education in Costa Rica. The study focused on identifying factors associated with the low enrollment rates  in the higher education system. A qualitative approach with phenomenological design was employed to explore, describe, and understand students’  experiences from their own perspectives. Data analysis was based on discourse analysis, critically comparing educational practice with theory from a critical point of view.  The findings highlight that students value the vocational guidance opportunities provided by educational institutions, which are aligned with the guidelines established by the Ministry of Public Education.